Emergent Online Teaching Effect on International Graduate Students’ Academic Performance in Japan during COVID-19 - Jiwon Jung; Chun Yee Wong (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
International graduate students reluctantly partook in the distance learning with the closure of national borders with the outbreak of COVID-19. Different instructional modes (in-person, online, and hybrid) and timing of the online learning exposure would play a role in international students’ academic achievement considering the expectations and motivations to learn abroad. Based on 267 course-based panel data, for the same courses, online-mode teaching yielded worse Grade Point Averages (GPAs) and less of a sense of class community compared to the in-person mode. Similarly, students who started the program after COVID-19 (i.e., Class of 2022) performed worse than those who changed their mode of study during their study due to COVID-19 (i.e., Class of 2021). The more frequent interactions with schoolmates and professors partially mediated this detrimental effect of international online learning. Online learning, on average, decreases the GPA by 0.2 standard deviations (p<0.05). However, this effect became insignificant in the model with the frequency of interacting with classmates or professors that raise the GPA by 0.686 and 0.216 standard deviations (p,0.05), respectively. As the study sheds light on the predicament of emergent distance learning, the study addresses some cautious notes on designing effective and sustainable international education in the post-pandemic era.